Avaliação de progênies dos cafés Catuaí Amarelo e Catuaí Vermelho na região de Pindorama (SP) - Martins, Antonio Lucio Mello (1992)
Four progenies of the Catuaí Amarelo and three of the Catuaí Vermelho cultivars of Coffea arabica L. were evaluated for yield, as well as fruits and seed characteristics in a trial carried out at Pindorama Experimental Station. Caturra Amarelo and Mundo Novo cultivars of the same specie were used as control. Latin square 9 x 9 design was used. Each plot had six double plants (two plants per hole) planted 3 x 2 m in apart. Individual plant yield was recorded throughout eighteen years (1971-1988). It was analysed also the relation of ripe fruit weight to clean coffee weight; percentage of empty fruits; percentage of flat, peaberry and elephant beans; seed size and weight of 100 seeds for each individual plant. The Catuaí Amarelo progeny CH 2077-2-5-62 gave the highest total yield and Caturra Amarelo LC 476 the lowest one. Yield oscillation was similar for the highest yielding Catuaí progenies and the Mundo Novo and Caturra Amarelo standards. The results indicated that the Catuaí Amarelo and Catuaí Vermelho can be successfully grown at the Pindorama region.